Latitude dependence of long-term geomagnetic activity and its solar wind drivers - M. Myllys; N. Partamies; N. Partamies; L. Juusola (Annales Geophysicae, 2015)
To validate the usage of global indices in studies of geomagnetic activity, we have examined the latitude dependence of geomagnetic variations in Fennoscandia and Svalbard from 1994 to 2010. Daily standard deviation (SD) values of the horizontal magnetic field have been used as a measure of the ground magnetic disturbance level. We found that the timing of the geomagnetic minimum depends on the latitude region: corresponding to the minimum of sunspot cycle 22 (in 1996), the geomagnetic minimum occurred between the geomagnetic latitudes 57–61° in 1996 and at the latitudes 64–67° in 1997, which are the average auroral oval latitudes. During sunspot cycle 23, all latitude regions experienced the minimum in 2009, a year after the sunspot minimum. These timing differences are due to the latitude dependence of the 10 s daily SD on the different solar wind drivers. In the latitude region of 64–67°, the impact of the high-speed solar wind streams (HSSs) on the geomagnetic activity is the most pronounced compared to the other latitude groups, while in the latitude region of 57–61°, the importance of the coronal mass ejections (CMEs) dominates. The geomagnetic activity maxima during ascending solar cycle phases are typically caused by CME activity and occur especially in the oval and sub-auroral regions. The strongest geomagnetic activity occurs during the descending solar cycle phases due to a mixture of CME and HSS activity. Closer to the solar minimum, less severe geomagnetic activity is driven by HSSs and mainly visible in the poleward part of the auroral region. According to our study, however, the timing of the geomagnetic activity minima (and maxima) in different latitude bands is different, due to the relative importance of different solar wind drivers at different latitudes.